Cinema e educação : produção e democratização do audiovisual com crianças e adolescentes em Curitiba - Stecz, Solange Straube (Universidade Federal de São Carlos, 2015)
The starting point of this study is the project "Children and Animated Film", held by the “Cinemateca de Curitiba” between 1976 and 1983 that innovated the relationship between cinema and education in municipal schools. Its innovative character, allow us to compare it to contemporary audiovisual projects, which production and enjoyment of work towards audiovisual democratization. The main view expressed here is that cinema in its artistic dimension, educational and humanistic builds bridges between educators and filmmakers working in the perspective of education as the practice of freedom. Evaluate the relationships between cinema and education requires us to pass beyond the awareness and criticality of the cinematic look of the children considering the school as a space for development and enjoyment of cinema as art. It also allow us think the role of the film-maker in school and how their technical knowledge / aesthetic contributes to the process. The main objective of this study is to reflect on the development of relations between cinema and the education in Curitiba, its practices and actors, with reference to the project, "Child and Animation Film" and contemporary experiences in audiovisual. The theory reference is based on education concepts, philosophy, sociology and anthropology, from key authors such as Alain Bergala, for whom the school should be a place of incorporation and enjoyment of cinema as art. Love the movie and understand it requires the adoption of a pedagogy of creation, not just of contemplation.
Keywords: Cinema; Educação; Descentralização da cultura; Education; Culture decentralization; LINGUISTICA, LETRAS E ARTES::ARTES::CINEMA::INTERPRETACAO CINEMATOGRAFICA; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO